Strategic Succession Plan to Expand the Sustainability of Saluyu Berkah Store: Linking and Integrating Education - Komalasari, Fira; Nurbayanti, Resti; Rifandi, Rifan Ahmad; Julajizah , Nita; Fauziyah, Azizah (CV. Tripe Konsultan, 2024)
The ability to endure and thrive is contingent upon the previous generation's preparedness in formulating a comprehensive strategy for the succession process. This study aims to identify the factors that influence business sustainability and to pinpoint effective strategies that successors can employ to enhance performance and competitive strength. The research utilizes a qualitative methodology, focusing on